2017
DOI: 10.7554/elife.27082
|View full text |Cite
|
Sign up to set email alerts
|

RNA polymerase II stalling at pre-mRNA splice sites is enforced by ubiquitination of the catalytic subunit

Abstract: Numerous links exist between co-transcriptional RNA processing and the transcribing RNAPII. In particular, pre-mRNA splicing was reported to be associated with slowed RNAPII elongation. Here, we identify a site of ubiquitination (K1246) in the catalytic subunit of RNAPII close to the DNA entry path. Ubiquitination was increased in the absence of the Bre5-Ubp3 ubiquitin protease complex. Bre5 binds RNA in vivo, with a preference for exon 2 regions of intron-containing pre-mRNAs and poly(A) proximal sites. Ubiqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 70 publications
(117 reference statements)
0
20
0
Order By: Relevance
“…Similarly, cellular concentration of polyadenylation factors has been linked to coupled alternative polyadenylation and splicing (Movassat et al 2016). Additional features contributing to cooperativity may include the local chromatin environment and/or changes in Pol II (Gunderson and Johnson 2009;Gunderson et al 2011;Patrick et al 2015;Milligan et al 2017;Neves et al 2017;Nissen et al 2017). An EM tomography study of the Balbiani ring 3 gene containing 38 introns suggested that only one spliceosome may associate with each nascent RNA at any given time (Wetterberg et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, cellular concentration of polyadenylation factors has been linked to coupled alternative polyadenylation and splicing (Movassat et al 2016). Additional features contributing to cooperativity may include the local chromatin environment and/or changes in Pol II (Gunderson and Johnson 2009;Gunderson et al 2011;Patrick et al 2015;Milligan et al 2017;Neves et al 2017;Nissen et al 2017). An EM tomography study of the Balbiani ring 3 gene containing 38 introns suggested that only one spliceosome may associate with each nascent RNA at any given time (Wetterberg et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Additional features contributing to cooperativity may include the local chromatin environment and/or changes in Pol II elongation and modifications (Gunderson and Johnson 2009;Gunderson et al 2011;Patrick et al 2015;Milligan et al 2017;Neves et al 2017;Nissen et al 2017). An EM tomography study of the Balbiani ring 3 gene containing 38 introns suggested that only one spliceosome may associate with each nascent RNA at any given time (Wetterberg et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, interference with splicing stimulates pausing at 5 ′ and 3 ′ SSs (Alexander et al 2010b;Chathoth et al 2014). A recent study has shown that the large subunit of Pol II (Rbp1) in yeast is modified by ubiquitination on lysines 452, 695, and 1246 and that Bre5, an RNA binding protein, recruits de-ubiquitinase activity to remove this modifica-tion on K1246 (Milligan et al 2017). A viable deletion of Bre5 or mutation of K1246 to arginine alters Pol II density in intron-containing gene bodies, raising the possibility that de-ubiquitination releases Pol II from splicing-associated pausing and affects the efficiency of splicing.…”
Section: The Coordination Of Splicing With Transcriptionmentioning
confidence: 99%